Examining The Ibra's Application in The Islamic Financing Product in The Malaysian Islamic Bank - Nurlia, Nurlia; Bengana, Mohamed; Supriadi, Fenni (Tujjar International Journal of Islamic Economics Development, 2023)
Ibra' (rebate) is a word used in Islamic banking that refers to Islamic banks offering refunds in exchange for the customer making an early settlement prior to a specified situation. After Bank Negara Malaysia issued a guideline on providing Ibra' to all Islamic financial institutions, the applicability of Ibra became widely accepted. There are several concerns that come from the use of ibra' and how ibra' has been implemented by Islamic banks, and this paper investigates these issues utilizing library research and case studies. Because of the Islamic banks' policy, real-world examples of how ibra' is used in Islamic banks are few. This paper traces and discusses that development.